Telaah Aspek-Aspek Yang Mempengaruhi Kesulitan Belajar Mahasiswa Di Sampit (Kasus Pada Mahasiswa Sekolah Tinggi Ilmu Ekonomi Sampit Dan Universitas Darwan Ali Tahun 2013) - Sutejo, Bambang (Jurnal Aplikasi Manajemen Pendidikan, 2013)
This research aims to determine the factors that affect student learning difficulties in Sampit. The numbers of population members are 730 people which are then taken of the number of 120 students to be sampled with accidental sampling method. The method of analysis used in this study is the factors analysis.Factor one (F1), formed from grain physical health and emotions that have a factor loading above 0.50, for so-called factor F1 of Health. Factor two (F2), called Social factors have formed from grains Close riends, with students and faculty relationship between student relationship. Factor of three (F3), called learning factor, because the items in it consists of grains Interests talent, How to lesson presentation by the lecturer and the lecture material of lesson. All of these variables have factor loading above 0.50. From the results of the study were found to contribute to higher education providers in managing the student in order to strengthen the institutional aspects of the campus and the quality of the alumni graduation at a later date.